2012
DOI: 10.1103/physrevd.85.031502
|View full text |Cite
|
Sign up to set email alerts
|

FlavorSU(4)breaking between effective couplings

Abstract: Using a framework in which all elements are constrained by Dyson-Schwinger equation studies in QCD, and therefore incorporates a consistent, direct and simultaneous description of light-and heavy-quarks and the states they constitute, we analyze the accuracy of SU (4)-flavor symmetry relations between πρπ, KρK and DρD couplings. Such relations are widely used in phenomenological analyses of the interactions between matter and charmed mesons. We find that whilst SU (3)-flavor symmetry is accurate to 20%, SU (4)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 46 publications
(66 reference statements)
8
58
1
Order By: Relevance
“…Our result g ρDD = 1.103 is also smaller than predictions based on the VMD model [31,32] where g ρDD = 2.52 − 2.8. Moreover, we found that g ρDD < g ρππ /2, which is of the opposite trend to the predictions based on QCD sum rules [39] and Dyson-Schwinger equations of QCD [40], but it agrees with that obtained with the 3 P 0 pair-creation model in the nonrelativistic quark model of Refs. [42,43].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our result g ρDD = 1.103 is also smaller than predictions based on the VMD model [31,32] where g ρDD = 2.52 − 2.8. Moreover, we found that g ρDD < g ρππ /2, which is of the opposite trend to the predictions based on QCD sum rules [39] and Dyson-Schwinger equations of QCD [40], but it agrees with that obtained with the 3 P 0 pair-creation model in the nonrelativistic quark model of Refs. [42,43].…”
Section: Discussionsupporting
confidence: 74%
“…In Ref. [40], using a model constrained by the DysonSchwinger equations of QCD, it was found that the relation g ρDD = g ρππ /2 is strongly violated at the level of 300% or more. In a recent follow up of that study within the same framework, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the magnitude found here is similar to the amount of SU (3)-flavour symmetry breaking observed in the difference between ρKK and ρππ couplings [64].…”
Section: B Secondary Kaon Transition Form Factorsupporting
confidence: 66%
“…We start with the study conducted in the context of a 3 P 0 quark-pair creation model with hadron wave functions obtained from a nonrelativistic quark model (NRQM) [18]. The results obtained with the 3 P 0 model are then contrasted with those obtained in a framework using Dyson-Schwinger (DSE) equations, in which all elements are constrained by studies of QCD phenomenology, incorporating a consistent, direct and simultaneous description of light-and heavy-quarks [19].…”
Section: Charm In Matter and The Dn Interactionmentioning
confidence: 99%
“…of F ABC (q 2 ) involves several interconnected steps [19]: (1) solution of the Dyson-Schwinger equation for the propagators of the light and heavy quarks; (2) with the the derived quark propagators, the meson bound-state amplitudes are obtained from solving Bethe-Salpeter equations -they are normalized such that the experimental values of masses and electroweak decays constants of the mesons are correctly reproduced; and, (3) the matrix element is obtained by evaluating a triangle graph involving the quark propagators and the Bethe-Salpeter amplitudes. Physically motivated and controlled approximations in some of the steps above were implemented, all tested in several previous studies using this approachdiscussion of the approximations and references to relevant work are given in Ref.…”
Section: Menu 2013mentioning
confidence: 99%